THE IMPACT OF EMPLOYEE RECRUITMENT AND SELECTION PROCESS ON EMPLOYEE PERFORMANCE AT PT. KERETA API INDONESIA: PENGARUH PROSES REKRUTMEN DAN SELEKSI KARYAWAN TERHADAP KINERJA KARYAWAN DI PT. KERETA API INDONESIA - Deva Bipasha Esha Shif Dasani; Endang Murti; Harianto (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
Human Resources (HR) in a company has an important role to achieve company goals because high employee performance makes it possible to achieve previous goals.Employee performance is very important because it shows how well employees are able to carry out the responsibilities that have been given to them. Therefore, appropriate, measurable, and definable criteria are required simultaneously. It is very important to implement recruitment and selection procedures to ensure employee performance that can help achieve company goals. This study aims to analyze the effect of the employee recruitment and selection process on employee performance at PT Kereta Api Indonesia Operation Area 7 Madiun. The method used is quantitative research, which aims to quickly describe the characteristics of individuals, conditions, or phenomena in a particular group, as well as determine the frequency of relationships between various symptoms in society. Data collection techniques include questionnaires, observation, and documentation. The population in this study amounted to 542 people, with a sample of 80 respondents. Data analysis was carried out using simple linear regression with the help of SPSS software. The results of the analysis show that the recruitment and selection process has a positive and significant effect on employee performance. The hypothesis regarding the recruitment variable (X) shows the value of tcount> ttable (6.903> 1.990) with a significance level of 0.000 < 0.05. This indicates that partially, the recruitment and selection process has a positive and significant impact on employee performance